2007
DOI: 10.1111/j.1460-9568.2007.05888.x
|View full text |Cite
|
Sign up to set email alerts
|

Netrin‐1 receptor‐deficient mice show enhanced mesocortical dopamine transmission and blunted behavioural responses to amphetamine

Abstract: The mesocorticolimbic dopamine (DA) system is implicated in neurodevelopmental psychiatric disorders including schizophrenia but it is unknown how disruptions in brain development modify this system and increase predisposition to cognitive and behavioural abnormalities in adulthood. Netrins are guidance cues involved in the proper organization of neuronal connectivity during development. We have hypothesized that variations in the function of DCC (deleted in colorectal cancer), a netrin-1 receptor highly expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
141
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(159 citation statements)
references
References 63 publications
18
141
0
Order By: Relevance
“…We have shown that small alterations to mPFC dopamine connectivity lead to sizeable changes in the pyramidal neuron morphology and excitability and, consequently, to changes in cognitive processing and responses to drugs of abuse (Grant et al, 2007;Manitt et al, 2011Manitt et al, , 2013Pokinko et al, 2014). Similarly, dopamine function in the human prefrontal cortex has been shown to play a critical role in higherorder cognitive processing, including behavioral inhibition and salience attribution, as well as in the regulation of subcortical reward circuitry (Robbins et al, 1994;Rogers et al, 1999;Tomasi et al, 2007;Goldstein and Volkow, 2011).…”
Section: Dcc-mediated Effects Of Amphetamine On the Sculpting Of Mpfcmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that small alterations to mPFC dopamine connectivity lead to sizeable changes in the pyramidal neuron morphology and excitability and, consequently, to changes in cognitive processing and responses to drugs of abuse (Grant et al, 2007;Manitt et al, 2011Manitt et al, , 2013Pokinko et al, 2014). Similarly, dopamine function in the human prefrontal cortex has been shown to play a critical role in higherorder cognitive processing, including behavioral inhibition and salience attribution, as well as in the regulation of subcortical reward circuitry (Robbins et al, 1994;Rogers et al, 1999;Tomasi et al, 2007;Goldstein and Volkow, 2011).…”
Section: Dcc-mediated Effects Of Amphetamine On the Sculpting Of Mpfcmentioning
confidence: 99%
“…DCC expression in dopamine neurons is high during early development and adolescence, in line with the maturational timeline of dopamine pathways. Interestingly, DCC expression is substantially lower during adulthood, suggesting that DCC signaling may play a different, more local, role in the adult brain (Osborne et al, 2005;Grant et al, 2007;Manitt et al, 2010;Reyes et al, 2013;Yetnikoff et al, 2007Yetnikoff et al, , 2010Yetnikoff et al, , 2011Yetnikoff et al, , 2013a. Using rodents, we showed that DCC signaling within the ventral tegmental area (VTA) dopamine neurons determines the extent of their innervation to the mPFC specifically during adolescence and, in turn, organizes the structure and function of mPFC local circuitries (Manitt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 DCC-deficient adult mice showed altered dopamine transmission and locomotor activity accompanied by reduced dendritic spine density in the cerebral cortex. 5 These findings show that DCC is a crucial molecule in the development of dopamine circuitry, and alterations in DCC levels can lead to cognitive and behavioral abnormalities in adulthood. 4,5 In EPHB1-knockout mice, there is a significant cell loss in the substance nigra pars reticulata, but there is no obvious change in the number of dopamine neurons in the substance nigra pars compacta.…”
mentioning
confidence: 89%
“…5 These findings show that DCC is a crucial molecule in the development of dopamine circuitry, and alterations in DCC levels can lead to cognitive and behavioral abnormalities in adulthood. 4,5 In EPHB1-knockout mice, there is a significant cell loss in the substance nigra pars reticulata, but there is no obvious change in the number of dopamine neurons in the substance nigra pars compacta. 6 Differential expression of NTNG1 could alter dopaminergic and glutamatergic circuitry.…”
mentioning
confidence: 89%